Cardiac safety of simultaneous anti-HER2 and anthracycline therapy. (February 2016) - Jafri, Mariam; Rea, Daniel
A long established oncological dogma requires that trastuzumab should not be given in combination with anthracyclines due to excessive synergistic cardiac morbidity. However, trastuzumab has been recently granted a license in the neoadjuvant setting with concurrent anthracylines. We discuss the role of anti-HER2 agents in breast cancer and their associated toxicities. Anthracycline chemotherapies are a central component of most adjuvant and neoadjuvant breast cancer regimens. Cardiac toxicity due to anthracyclines is explored. Finally, in this article, we will discuss the evidence for concurrent administration of anthracyclines and HER2-targeted agents.